Controlling Pollution : Using Taxes and Tradable Permits - Reppelin, Valerie; Norregaard, John. (Washington, D.C. : International Monetary Fund, 2001)
Explores different ways of controlling pollution through -green-taxes or permits, and evaluates their advantages and disadvantages. While many countries use environmental taxes, interest in tradable permits is growing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United States